Skills of Students Asking in Learning Clasical Format - Deliani, Nurfarida; Prayitno, Prayitno; Yusuf, A. Muri; Jamna, Jamaris (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Learning is characterized by the use of good questioning skills , especially in learning for large groups of children. Skills in question play an important role in student learning activities. The low skill of students asking in the learning process can lead to disruption of an effective learning process and must be handled by the BK teacher appropriately. Questions are one of the stimuli of thinking that is good for teaching students. The research method used is R & D (Research and Development) by following the steps in developing the ADDIE pattern (Analyze, Design, Development, Implementation, Evaluation). The subject of the research trial consisted of experts to test the feasibility of the model, the BK teacher to assess the suitability of the model, and students to test the effectiveness. The study was conducted by collecting initial data as a material for consideration in preparing the initial model which was then tested for its suitability and effectiveness through Focus Group Discussion (FGD) and expert testing. The results of this study show that the students' skills in question are in the high category.